The medium, the message and the measure: A theory-driven review on the value of telehealth as a patient-facing digital health innovation - Seye Abimbola; Sarah Keelan; Michael Everett; Kim Casburn; Michelle Mitchell; Katherine Burchfield; Alexandra Martiniuk (Health Economics Review, 2019)
By what measure should a policy maker choose between two mediums that deliver the same or similar message or service? Between, say, video consultation or a remote patient monitoring application (i.e. patient-facing digital health innovations) and in-person consultation? To answer this question, we sought to identify measures which are used in randomised controlled trials. But first we used two theories to frame the effects of patient-facing digital health innovations on - 1) transaction costs (i.e. the effort, time and costs required to complete a clinical interaction); and 2) process outcomes and clinical outcomes along the care cascade or information value chain, such that the 'value of information' (VoI) is different at each point in the care cascade or value chain. From the trials, we identified three categories of measures: outcome (process or clinical), satisfaction, and cost. We found that although patient-facing digital health innovations tend to confer much of their value by altering process outcomes, satisfaction, and transaction costs, these measures are inconsistently assessed. Efforts to determine the relative value of and choose between mediums of service delivery should adopt a metric (i.e. mathematical combination of measures) that capture all dimensions of value. We argue that 'value of information' (VoI) is such a metric - it is calculated as the difference between the 'expected utility' (EU) of alternative options. But for patient-facing digital health innovations, 'expected utility' (EU) should incorporate the probability of achieving not only a clinical outcome, but also process outcomes (depending on the innovation under consideration); and the measures of utility should include satisfaction and transaction costs; and also changes in population access to services, and health system capacity to deliver more services, which may result from reduction in transaction costs.
Keywords: 330; Telehealth; Digital health; Value of information; Utility; Transaction costs; Satisfaction; Innovation